Redox behaviour of (CuO)sub(0.15)(CeOsub2)sub(0.85) mixed oxide catalyst prepared by sol-gel peroxide method - Pintar, Albin (Acta chimica slovenica, 2005)
Temperature-programmed reduction (TPR), oxidation (TPO) and desorption (TPD) studies were performed on (CuO)0.15(CeO2)0.85 copper-ceria mixed oxide sample prepared by sol-gel peroxide route. The obtained results reveal that despite initial drop in specific surface area after consecutive redox cycles the hydrogen consumption remains constant. This is because CuO is highly dispersedover the surface of CeO2 nano-crystallites and remains highly dispersed even after the agglomeration of CeO2 nano-crystallites in more densesecondary structure. The dispersed CuO is reduced to Cu0 during the TPR, forming agglomerated metal particles on the surface of partially reduced CeO2.After subsequent TPO step all the Cu0 is oxidized back into CuO and re-dispersed over the CeO2 crystallites.
Keywords: bakrovi oksidi; cerijevi oksidi; karakterizacija; kovinski oksidi; sinteza; sol-gel postopki